Tenodéza - řešení chronické nestability distálního radioulnárního kloubu - Lisý, Miroslav; Pink, Miloslav; Skládal, Martin; Vaňo, M (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2009)
Distal radioulnar joint (DRUJ) instability often develops after distal forearm fracture or severe dislocation of the wrist with damage to its stabilising structures. The instability is usually diagnosed as a chronic condition and only rarely at the time of injury. When the stabilising structures are not treated adequately soon after injury, instability develops and is accompanied with pain, restricted range of motion and reduced grip strength. This study presents the option of chronic instability treatment by tenodesis with use of the palmaris longus tendon. Its aim is to remind the broad medical community of this issue. MATERIAL Between July 1994 and November 2000, tenodesis was performed in 15 patients with chronic DRUJ instability. The right and left sides were affected in 10 and five patients, respectively; of them 12 were dominant extremities. All injuries were diagnosed as dorsal subluxation of the ulnar head, with side dislocation in three patients. METHODS The diagnosis was based on a thorough medical history, and clinical and radiographic examination, including projections in forced maximum radial and ulnar duction, as recommended by Geyer and Luzius as early as in 1964. Tenodesis was done by the Jäger and Wirth method using the palmaris longus tendon. The patients were scored according to the Modified Mayo Wrist System. RESULTS Of the 15 patients treated by this method, 14 were evaluated. Eight patients regarded the results as very good, with no pain at maximal physical activity, and five considered them good, experiencing pain only at maximal but not at everyday activities. One patient reported a poor outcome. The average score increased from pre-operative 40 to 60 points post-operatively. All patients had a slight restriction of rotation movements of the forearm. Residual instability was found in one patient. DISCUSSION It is a common view that this condition is caused by subluxation or dislocation of the ulnar head, while in fact it is subluxation or dislocation of the radius turning around the ulna. As reported in the literature, dorsal dislocation is three-times as frequent as volnar dislocation, and this is in agreement with our findings. There is a wide variety of the operative methods for tenodesis which differ in the distribution of tunnels in bone. Restriction of the range of motion in our patients also agreed with the literature data. No effect of a distal radius fracture on the results of surgery was recorded. CONCLUSIONS Our results show that tenodesis is a method suitable to treat chronic DRUJ instability if the indication criteria are observed, i. e., if no arthritic lesions are present in the joint.
Keywords: nestabilita kloubu; Ulna; zápěstní kloub; Male; chronická nemoc; Adult; Wrist Joint; dospělí; mužské pohlaví; Chronic Disease; Radius; Tenodesis; šlachy; Joint Instability; lidé; ženské pohlaví; tenodéza; Humans; radius; ulna; Female; Tendons